Sarana Belajar Anak Usia Dini: Bagaimana Persepsi Orangtua pada Penggunaan Gadget? - Indah Maysela Azzahra; Hasti Yustina; Ibrahim Ibrahim (AWLADY : Jurnal Pendidikan Anak, 2023)
Parents complain that the online learning method using gadgets as a means of learning for children is difficult to understand and use. The purpose of the study is to describe information about parents' perceptions of the use of gadgets as a means of learning for early childhood in the city of Palembang. The research method uses quantitative research methods with a survey approach, which is addressed to parents by providing a statement using a google form questionnaire instrument. The research population is all parents who have chilhood early in the city of Palembang. While the research sample selected using a purposive sampling technique was 50 parents with the criteria of parents sending their children to PAUD Palembang City and carrying out partly face-to-face learning and partly online learning. Data collection techniques used are observation and interviews. The data analysis technique uses quantitative data analysis techniques. The results showed that 38% of parents were able to use and teach their children while studying at home using the WhatsApp and Google Classroom applications, 26% of parents were able to use and teach their children while studying at home using the YouTube, Google and Social Media applications, 20% respondents who can use and teach their children when studying at home with educational game applications in gadgets, and 16% of parents who can use and teach their children while studying at home with zoom and google meet applications. Basically, parents can use gadgets as a means of learning for their children, but in certain applications such as zoom and google meet, parents still have difficulty using the application and when parents help their children learn online. So that parents prefer and easily use applications such as whatsapp and google classroom for children's online learning media at home.